Directive Speech Acts in Lanang Setiawan’s Poems - Mualimin Mualimin (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
Directives are utterances intended for the listeners or readers to do something as desired by the speaker or the author. Poem as one of the literary works is the expression of the author delivered to the readers. As an expression of the author's, poems probably contain more expressive utterances than the directive ones. This paper attempts to examine poems written by Lanang Setiawan, a local writer from Tegal who wrote lots of poems in the Javanese dialect of Tegal. The poems written by Lanang will be used as data to be analyzed by using pragmatic theory.Keywords: directive speech acts, Javanese  language of Tegal, Tegal literature